Exploring nutrient management options to increase nitrogen and phosphorus use efficiencies in food production of China. (June 2018) - Wang, Mengru; Ma, Lin; Strokal, Maryna; Chu, Yanan; Kroeze, Carolien
Abstract: Low nitrogen (NUE) and phosphorus (PUE) use efficiencies in food production in China result in large losses of nitrogen (N) and phosphorus (P) to the environment. The Chinese government formulated policies to increase the NUEs and PUEs. Recent policies aim for zero growth in synthetic fertilizer use after 2020 while ensuring food security. In this study we analyzed how current and improved nutrient management in China can affect future nutrient use efficiencies and nutrient losses from food production. The NUEs and PUEs of food production were quantified using the NUFER (NUtrient flows in Food chains, Environment and Resources use) model for 31 provinces and China in 2013, 2020 and 2050. Results show that national NUE (20%) and PUE (24%) in 2013 are low but vary largely among provinces (12–33% for NUE, 10–53% for PUE). The N and P losses to the air (14 Tg year − 1 of N) and waters (12 Tg year − 1 of N, 2 Tg year − 1 of P) are consequently high in 2013. Three scenarios were analyzed for 2020 and 2050 to explore future trends in NUEs and PUEs, assuming Business As Usual ( BAU ) trends, Zero Fertilizer ( ZF ) growth from 2020, and Improved Nutrient Management ( INM ). In the BAU scenario, the NUEs and PUEs roughly remain at their low 2013 levels, while nutrient inputs to agriculture are increasing. The losses to the air therefore increase by 37% for N and to waters by 40% for N and 48% for P between 2013 and 2050. In the ZF scenario, the NUEs and PUEs are a few percent higher than in BAU . The associated N and P losses to waters are 8–16% lower than in BAU because of increased recycling of manure to cropland, but still higher than in 2013. Improved nutrient management, as assumed in our INM scenario, may increase NUEs and PUEs to 33% and 59% in 2050. Meanwhile, N and P losses to waters in 2050 are 47% and 83% lower than in 2013, and losses of N to the air 20% lower. We conclude that the policy aimed at zero growth in fertilizer use is a good start, but not very effective in reducing nutrient pollution in China. To substantially reduce N and P losses to the environment it is needed to improve nutrient management by not only reducing fertilization without yield losses, but also by improved manure management and animal production with lower nutrient excretion. Highlights: N and P use efficiencies in Chinese food production were low in 2013. N and P losses from food production to the environment were high in 2013. N and P use efficiencies in Chinese food production will likely decrease by 2050. Current policies are not very effective to improve N and P use efficiencies. Improved nutrient management is needed for sustainable food production in China.